Role of hepatitis c virus in hepatocellular carcinoma and neurological disorders: an overview - Suhail, Mohd; Sohrab, Sayed Sartaj; Kamal, Mohammad Amjad; Azhar, Esam Ibraheem (Frontiers in Oncology, 2022)
The hepatitis C virus (HCV) causes serious issues, affecting 71 million people globally. The most common manifestations range from chronic hepatitis to liver cirrhosis, leading to hepatocellular carcinoma. Many mechanisms are known to play an important role in HCV-induced HCC. The interaction of viral proteins with host cells results in oxidative stress damage, liver inflammation, and irregularities in signaling pathways. These results in the activation of oncogenes and metabolic disturbances, liver fibrosis, and angiogenesis. Additionally, some non-coding RNAs (ncRNAs) and toll-like receptors have been identified and play a significant role in HCC development. This virus is also associated with impairment of the central nervous system, resulting in acute or sub-acute encephalopathy and inflammatory disorders. Neurological disorders are associated with the inflammatory responses of many cells, including microglia and astrocytes. Additionally, there are many other extrahepatic manifestations, including neurological disorders such as depression and fatigue, in 50% of infected patients. These manifestations include neuro-invasion, immune-mediated damage, neurotransmitter alterations, sensory-motor polyneuropathy, sensitivity loss, weakness of the leg, and cryoglobulinemia, which significantly results in a reduced quality of life. HCV infection may be improved using an appropriate diagnosis and direct antiviral therapy for sustained virological response. However, the success of therapy depends on the symptoms and organ damage, diagnosis, and therapeutic strategies applied. Some published reports have discussed that HCV is associated with both HCC and neurological disorders. Additionally, it has also been observed that individuals with HCC also develop neurological disorders compared with individuals with HCV alone. This review aims to provide an overview of the latest information about the relationship between HCV-induced HCC and their role in neurological disorders. Additionally, we have also discussed the progress made in the diagnosis, physio-pathological mechanisms, and strong antiviral therapies developed for HCV infection and HCC, as well as the latest advancements made in the study of the neurological disorders associated with HCV infection.